Selenomethionine alleviates OTA-induced kidney injury in broilers by modulating ferroptosis - Tian, Wenqi; Fan, Ruiwen; Zhou, Shuqin; Liu, Tao; Wang, Yongdong; Sun, Yuhang; Long, Miao; Yang, Shuhua; Li, Peng (Frontiers in Veterinary Science, 2025)
Mycotoxin contamination in food and feed poses a significant threat to human and animal health worldwide. OTA is a common mycotoxin. About 20–30% of global feed is contaminated with OTA, and the annual potential contamination amount exceeds 200 million tons, which has become a major problem of local feed safety. OTA shows strong nephrotoxicity and causes kidney damage in animals and humans. Growing evidence suggests that OTA-induced renal damage is closely associated with ferroptosis. Selenomethionine (SeMet), as the main chemical form of daily dietary selenium supplementation, has pharmacological properties such as anti-oxidation, anti-inflammatory, anti-mutagenic, anti-cancer, anti-viral and anti-bacterial, which can effectively inhibit the nephrotoxicity of OTA. This study aims to establish an OTA-induced broiler kidney injury model and implement selenium-containing methionine intervention. Utilizing transmission electron microscopy, qRT-PCR, and immunoblotting techniques, the research will analyze pathological changes in broiler kidneys, examine ultrastructural alterations, and evaluate gene/protein expressions of renal function indicators, ferroptosis biomarkers, inflammatory-related parameters, and Nrf2-GPX4 signaling pathway components. This study aimed to investigate whether SeMet alleviates OTA-induced kidney injury in broilers by regulating ferroptosis and to elucidate the underlying mechanisms. Results showed that OTA caused renal histopathological alterations, elevated serum concentrations of urea nitrogen (BUN), creatinine (CRE), uric acid (UA), and pro-inflammatory cytokines (IL-1β and IL-6). OTA also increased reactive oxygen species (ROS), malondialdehyde (MDA), and ferrous ion (Fe2+) levels while reducing total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and reduced glutathione/oxidized glutathione (GSH/GSSG). Additionally, OTA upregulated mRNA and protein levels of transferrin receptor 1 (TFR1) and kelch like ech-associated protein 1 (Keap1), while downregulating the nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1), quinone oxidoreductase-1 (NQO1), glutathione peroxidase 4 (GPX4), ferritin heavy chain 1 (FTH1), and solute carrier family 7 member 11 (SLC7A11), thereby inducing lipid peroxidation and ferroptosis. By reversing the above changes induced by OTA, SeMet alleviated OTA-induced renal injury and inhibited OTA-induced lipid peroxidation and ferroptosis. These findings indicate that SeMet alleviates OTA-induced renal injury by inhibiting ferroptosis, suggesting that SeMet can be used as a feed additive in mycotoxin-contaminated environments.